Collective action, property rights and risk - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Poverty or well-being is determined not only by the assets and income of a household, but also by its degree of vulnerability to risks and shocks. Risks can be characterized by their frequency and probability; some occur frequently (rainfall variation), some with less frequency (elections resulting in change in government), and others rarely (revolutions, earthquakes). The more frequent the occurrence, the more likely that people know the distribution of possible outcomes and, thus, the probabilities of specific outcomes.